Bacterial Indicators Are Ubiquitous Members of Pelagic Microbiome in Anthropogenically Impacted Coastal Ecosystem - Orel, Neža; Fadeev, Eduard; Klun, Katja; Ličer, Matjaž; Tinta, Tinkara; Turk, Valentina (Frontiers in Microbiology, 2022)
Coastal zones are exposed to various anthropogenic impacts, such as different types of wastewater pollution, e.g., treated wastewater discharges, leakage from sewage systems, agricultural and urban run-off. These various inputs can introduce allochthonous organic matter and microbes, including pathogens, to the coastal marine environment. The presence of fecal bacterial indicators in coastal environments is usually monitored using traditional culture-based methods that, however, fail to detect their uncultured representatives. We have conducted a year-around in situ survey of the pelagic microbiome of the dynamic coastal ecosystem, subjected to different anthropogenic pressures, to depict the seasonal and spatial dynamics of traditional and alternative fecal bacterial indicators. To provide an insight into environmental conditions under which bacterial indicators thrive, a suite of environmental factors and bacterial community dynamics was analyzed concurrently. Analyses of 16S rRNA amplicon sequences revealed that coastal microbiome was primarily structured by seasonal changes, regardless of the distance from wastewater pollution sources. On the other hand, fecal bacterial indicators were not influenced by seasons and accounted up to 34 % of the sequence proportion for a given sample. Even more so, traditional fecal indicator bacteria (Enterobacteriaceae) and alternative wastewater-associated bacteria (Lachnospiraceae, Ruminococcaceae, Arcobacteraceae, Pseudomonadaceae and Vibrionaceae) were part of the core coastal microbiome, i.e., present at all sampling stations. The microbial source tracking and Lagrangian particle tracking we employed to assess the potential pollution source revealed the importance of riverine water as vector for transmission of allochthonous microbes into marine systems. Further phylogenetic analysis showed that the Arcobacteraceae in our dataset affiliated with the pathogenic Arcobacter cryaerophilus, suggesting that a potential exposure risk to bacterial pathogens in anthropogenically-impacted coastal zones remains. We would like to emphasize that molecular analyses combined with statistical and oceanographic models may provide new insights for environmental health assessment and reveal the potential source and presence of microbial indicators, which are otherwise overlooked by a cultivation approach.